Penetration Depth of Propylene Glycol, Sodium Fluorescein and Nile Red into the Skin Using Non-Invasive Two-Photon Excited FLIM - Mohammad Alhibah; Marius Kröger; Sabine Schanzer; Loris Busch; Jürgen Lademann; Ingeborg Beckers; Martina C. Meinke; Maxim E. Darvin (MDPI AG, 2022)
The stratum corneum (SC) forms a strong barrier against topical drug delivery. Therefore, understanding the penetration depth and pathways into the SC is important for the efficiency of drug delivery and cosmetic safety. In this study, TPT-FLIM (two-photon tomography combined with fluorescence lifetime imaging) was applied as a non-invasive optical method for the visualization of skin structure and components to study penetration depths of exemplary substances, like hydrophilic propylene glycol (PG), sodium fluorescein (NaFl) and lipophilic Nile red (NR) into porcine ear skin ex vivo. Non-fluorescent PG was detected indirectly based on the pH-dependent increase in the fluorescence lifetime of SC components. The pH similarity between PG and viable epidermis limited the detection of PG. NaFl reached the viable epidermis, which was also proved by laser scanning microscopy. Tape stripping and confocal Raman micro-spectroscopy were performed additionally to study NaFl, which revealed penetration depths of ≈5 and ≈8 μm, respectively. Lastly, NR did not permeate the SC. We concluded that the amplitude-weighted mean fluorescence lifetime is the most appropriate FLIM parameter to build up penetration profiles. This work is anticipated to provide a non-invasive TPT-FLIM method for studying the penetration of topically applied drugs and cosmetics into the skin.